2015
DOI: 10.1039/c5tx00043b
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy as the effector and player in DNA damage response of cells to genotoxicants

Abstract: Autophagy is a highly conserved pathway in eukaryotic cells induced by a variety of stimuli to remove superfluous or damaged organelles or abnormally aggregated proteins to maintain cellular homeostasis.A remarkable progress in our understanding of autophagy has been made in the past decade, not only regarding the molecular mechanism, but also its fundamental roles in the biological effects of various environmental stresses or the development of some human diseases. The genome of eukaryotic cells is constantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 118 publications
1
17
0
Order By: Relevance
“…The regulators of autophagy can be grouped as inducers (activators) or inhibitors (reducers), which counter balance and lead cells to a normal state or autophagy [ 31 ]. Upstream regulators include mammalian target of rapamycin (mTOR), phosphatidylinositol-4,5-bisphosphate 3-kinase-p85 (PI3K-p85), and protein kinase B (Akt) as inhibitors, and Beclin-1 and PI3K-Class III (PI3K-III) as inducers [ 32 ]. The following section examines the upstream regulating mechanism of PG-induced autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…The regulators of autophagy can be grouped as inducers (activators) or inhibitors (reducers), which counter balance and lead cells to a normal state or autophagy [ 31 ]. Upstream regulators include mammalian target of rapamycin (mTOR), phosphatidylinositol-4,5-bisphosphate 3-kinase-p85 (PI3K-p85), and protein kinase B (Akt) as inhibitors, and Beclin-1 and PI3K-Class III (PI3K-III) as inducers [ 32 ]. The following section examines the upstream regulating mechanism of PG-induced autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy is a lysosomal degradation pathway in eukaryotic cells activated by variety of chemical and physical stresses such as ionizing radiation. There are plenty of reports demonstrating that autophagy leads to dual effects of protecting cells survival and promoting cells death under different cellular condition 28 29 . Recently, Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a lysosomal degradation pathway in eukaryotic cells activated by variety of stimuli to recycle obsolete cellular components and remove the damaged proteins and organelles. Autophagy is reported to have a cytoprotective role in response to various forms of cellular stresses, including deprivation of nutrients, hypoxia and genotoxic agents, such as ionizing radiation 26 27 28 . Despite its predominant function as a potential survival mechanism, accumulating data also demonstrated that autophagy represents a pathway contributing to cell death 28 29 .…”
mentioning
confidence: 99%
“…Obviously, the DNA damage response (DDR) of intricate molecular signals networks is immediately triggered after irradiation, and a series of cellular responses are evolved to counteract DNA damage and cell injury. The early cellular responses, initiated immediately and persisted for 24h or longer after irradiation, include DNA repair, cell cycle arrest, apoptosis, autophagy, etc [ 58 , 59 ]. In presented study, the proteomic expression profiles were identified 4h post-irradiation, at which time the DNA repair was still undergoing, and cell cycle arrest, cell death or survival signals could also be initiated.…”
Section: Discussionmentioning
confidence: 99%